2000
DOI: 10.1006/dbio.2000.9860
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death in Zebrafish Rohon Beard Neurons Is Influenced by TrkC1/NT-3 Signaling

Abstract: Rohon Beard (RB) cells are embryonic primary sensory neurons that are removed by programmed cell death during larval development in zebrafish. RB somatosensory functions are taken over by neurons of the dorsal root ganglia (DRG), suggesting that RB cell death may be triggered by the differentiation of these ganglia, as has been proposed to be the case in Xenopus. However, here we show that the timing of RB cell death correlates with reduced expression of trkC1, the receptor for neurotrophin NT-3, but not with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 36 publications
3
105
2
Order By: Relevance
“…Previous studies provided evidence that zebrafish RBs undergo programmed cell death and are essentially gone by the end of 3d (Williams et al, 2000;Svoboda et al, 2001;Cole and Ross, 2001). Thus, we were surprised that our labeled cells remained for as long as 7d.…”
Section: Rbs Fragment Their Dna Before Overt Cellular Degenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies provided evidence that zebrafish RBs undergo programmed cell death and are essentially gone by the end of 3d (Williams et al, 2000;Svoboda et al, 2001;Cole and Ross, 2001). Thus, we were surprised that our labeled cells remained for as long as 7d.…”
Section: Rbs Fragment Their Dna Before Overt Cellular Degenerationmentioning
confidence: 99%
“…In zebrafish, some RBs fragment their DNA before DRG axogenesis, thus Williams et al (2000) suggested it was unlikely that early RB death is due to direct interactions with DRG neurons. However, the possibility remains that some interaction with DRG neurons triggers later-occurring RB death.…”
Section: Rb Cell Death Is Independent Of Drg Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Zebrafish RB neurons are the equivalent of the amphibian RB neurons, having large cell bodies with huge nuclei and granular cytoplasm (Metcalfe et al, 1990). Although zebrafish RB neurons begin showing signs of programmed cell death, such as DNA fragmentation, as early as the first day of development, the cells remain present for considerably longer and degenerate over a protracted period of time and unlike in amphibians, independent of any developmental link to DRG neurons (Williams et al, 2000).…”
Section: Introductionmentioning
confidence: 99%